Effects of soil type and composition of rhizodeposits on rhizosphere priming phenomena - Lloyd, D.; Ritz, Karl; Paterson, E.; Kirk, Guy J. D. (Elsevier, 2016)
Inputs of fresh plant-derived C may stimulate microbially-mediated turnover of soil organic matter (SOM) in the rhizosphere. But studies of such ‘priming’ effects in artificial systems often produce conflicting results, depending on such variables as rates of substrate addition, substrate composition, whether pure compounds or mixtures of substrates are used, and whether the addition is pulsed or continuous. Studies in planted systems are less common, but also produce apparently conflicting results, and the mechanisms of these effects are poorly understood. To add to the evidence on these matters, we grew a C4 grass for 61 d in two contrasting soils – an acid sandy soil and a more fertile clay-loam – which had previously only supported C3 vegetation. We measured total soil respiration and its C isotope composition, and used the latter to partition the respiration between plant- and soil-C sources. We found SOM turnover was enhanced (i.e. positive priming) by plant growth in both soils. In treatments in which the grass was clipped, net growth was greatly diminished, and priming effects were correspondingly weak. In treatments without clipping, net plant growth, total soil respiration and SOM-derived respiration were all much greater. Further, SOM-derived respiration increased over time in parallel with increases in plant growth, but the increase was delayed in the less fertile soil. We conclude the observed priming effects were driven by microbial demand for N, fuelled by deposition of C substrate from roots and competition with roots for N. The extent of priming depended on soil type and plant growing conditions. In a further experiment, we simulated rhizodeposition of soluble microbial substrates in the same two soils with near-continuous additions for 19 d of either C4-labelled sucrose (i.e. a simple single substrate) or a maize root extract (i.e. a relatively diverse substrate), and we measured soil respiration and its C isotope signature. In the more fertile soil, sucrose induced increasingly positive priming effects over time, whereas the maize root extract produced declining priming effects over time. We suggest this was because N and other nutrients were provided from the mineralization of this more diverse substrate. In the less-fertile soil, microbial N demand was probably never satisfied by the combined mineralization from added substrate and soil organic matter. Therefore priming effects were approximately constant over time. We conclude that the chemical nature of putative priming compounds can greatly influence priming phenomena.
Keywords: Priming effect; Soil organic matter; Rhizosphere; C4 grass; Stable isotopes